1999
DOI: 10.1063/1.479946
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous nucleation rates of supercooled water measured in single levitated microdroplets

Abstract: Homogeneous nucleation rates are determined for micrometer sized water droplets levitated inside an electrodynamic Paul-trap. The size of a single droplet is continuously measured by analyzing the angle-resolved light scattering pattern of the droplets with classical Mie theory. The freezing process is detected by a pronounced increase in the depolarization of the scattered light. By statistical analysis of the freezing process of some thousand individual droplets, we obtained the homogeneous nucleation rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
203
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(215 citation statements)
references
References 45 publications
(47 reference statements)
10
203
0
1
Order By: Relevance
“…4͒. The optical arrangement is similar to that reported by Krämer et al 10 A collimating lens fastened directly to the chamber in place of a window minimizes Fabry-Pérot interference that would result from passing the spherical wave front through the two parallel flat surfaces of a window. A second lens focuses the scattered light through an aperture ͑approximately 1.5 mm͒ to filter off-axis radiation and a third lens recollimates the light onto the CCD detector of a video camera.…”
Section: Collection Of Angular Light Scatteringsupporting
confidence: 54%
See 3 more Smart Citations
“…4͒. The optical arrangement is similar to that reported by Krämer et al 10 A collimating lens fastened directly to the chamber in place of a window minimizes Fabry-Pérot interference that would result from passing the spherical wave front through the two parallel flat surfaces of a window. A second lens focuses the scattered light through an aperture ͑approximately 1.5 mm͒ to filter off-axis radiation and a third lens recollimates the light onto the CCD detector of a video camera.…”
Section: Collection Of Angular Light Scatteringsupporting
confidence: 54%
“…13 When, for example, Krämer et al 10 systematically varied the temperature, the measured ice crystal nucleation rate increased by a factor of 70 as the temperature was reduced by just 1 K. Precise control of the thermodynamic state is thus critical to the measurement of nucleation rates. Only able to regulate the relative humidity ͑RH͒ within ±0.5% RH during repeated experiments, Hamza et al 9 reported nucleation rates that varied by a factor of 300.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,56 In this study, we have selected a subset [56][57][58][59][60][61][62][63][64][65][66][67][68] of the available data sets for the purposes of constraining the new parameterization. The criteria for selection were (i) minimal and well defined uncertainties, (ii) good reproducibility within the data set, and (iii) an internal droplet pressure of about 1 bar.…”
Section: Fitting the Cnt-based Model To Experimental Datamentioning
confidence: 99%